Reputation of public organizations: What dimensions are crucial? - Galv\~ao Meirinhos; Maximino Bessa; Carmem Pereira Leal; Márcio José Sol Pereira Oliveira; Amélia Carvalho; Rui Silva (Administrative Sciences, 2022)
This paper explores the relationships among variables and determines the influences of dimensions (i.e., municipal satisfaction, organizational performance, perceived quality, contestations and complaints of the municipal executive) on the notoriety, image, and reputation (NIR) of municipal executives. We attempted to understand if citizens' opinions influenced the evaluations, recommendations, and contestations based on NIR. Parishes in the municipality of Valongo were selected and analysed, namely Alfena, Campo e Sobrado, Valongo, and Ermesinde; a total of 998 questionnaires were collected. It was concluded that all of the studied dimensions were statistically significant in the final structural estimated model. The structural results point to municipal satisfaction and contestations and complaints of municipal executives as having directly positive and statistically significant influences on NIR. Organizational performance and perceived quality have directly positive but not statistically significant influences on NIR. The results of this research suggest that obtaining the personal opinions of citizens (e.g., regarding the work performances of their mayors) allows citizens to feel heard and active in their municipalities. From the point of view of public executives, the results of this type of study could provide valid information that allows stakeholders to make political decisions that are appropriate for the interests of their communities (e.g., by listening to their citizens).
Keywords: 350; contestation and complaint; image; municipal satisfaction; notoriety; organizational performance; organizational reputation; perceived quality; public organizations; reputation